Effect of a didactic proposal on strength and flexibility in a sample of skateboarders - Becerra-Patino, B.; Ortiz-Quezada, V.; Chaves-Cardenas, J.; Pachon-Canas, J.; Ramirez-Alvarado, J. S. (Journal of Physical Education and Sport, 2022)
Background: speed skating continues to expand its research needs, given the growing interest in knowing the factors related to sports performance at early ages. Objective: to evaluate the effect of a didactic proposal oriented towards the development of strength and flexibility, seeking to improve the technical foundation of the spagatta in a sample of Colombian skaters aged 12 and 13 years old. Method: The selected sample comprised 18 children between 12 and 13 years of age (transition category) with an age of 12.55±0.68 years, a body mass of 44.94±6.68 kilograms and a height of 153.49±7.12 centimeters, who were divided into a control group (n:9) and an experimental group (n:9). Quantitative approach study, quasi-experimental design and descriptive study type, with a pseudo-random intentional sampling. Quantitative approach study, descriptive study type and quasiexperimental design. The statistical data were processed using the ® program version 4.1.0 in different phases; descriptive analysis, an Anova analysis of variance and the correlation method. The significance value was set at p value <0.01. Results: In relation to the objective established for the present investigation, significant differences were found for each of the variables under study, related to the static test right leg front Spagatta p=0.000, static left leg front Spagatta p=0.000, Squa Jump p=0.004, flexibility in the Sit and Reach test p=0.001 and in Kinovea p=0.000 to measure the technical foundation of the spagatta. Discussion: Thus, the didactic proposal of the present research is based on the search for alternatives for learning the technical basis of spagatta. In this sense, there are several investigations aimed at the variability of methods to promote learning in speed skating. Conclusion: The effect of the didactic proposal focused on the development of strength and flexibility for the improvement of the technical foundation of the spagatta in skaters of 12 and 13 years old, was effective, significantly improving the strength, flexibility and amplitude of the skater's technical foundation.